On the choice of fluid for the hydration of middle-aged marathon runners. Issue 1 (April 1977) - Kavanagh, T.; Shephard, R. J.
Abstract : Nine subjects (five well-trained post-coronary patients and four other middle-aged joggers) paticipated in a 42 km "Marathon" race. The course was covered in an average of 212 minutes under pleasantly warm conditions (Maximum 21.7 degree C, 69% relative humidity). Subjects were given initial hyperhydration and repeated subsequent doses of water, "Erg" (Na+ 19mE/l K+ 10.7mE/l, glucose 5.3g/100 ml) or a "Special Solution" (during the race Na+ 21mE/1 glucose 4.1g/100 ml; after the race Na+ 20 mE/l, K+ 4.7mE/l., glucose 4.1 g/100 ml). Weight loss averaged 2.2 kg and sweat production 3.3l taking account of water liberated from the hydration of glycogen and the oxidation of food stuffs, it was estimated that most subjects suffered relatively little dehydration over the race (0.4--0.8l). This was confirmed by a sustained urine production of greater than 100ml/hr. Nevertheless, rectal temperatures showed substantial elevation over the race (final readings 38.3 - 40.2 degree C). In terms of fluid balance and stability of plasma mineral composition, the runners drinking water performed slightly better than those receiving the other two solutions. Nevertheless, there may be merit in giving potassium solutions during recovery from vigorous effort.